Blended learning in ESL courses: UiTM students' attitudes and perceptions / Rosita Aminullah, Roselina Musahar and Nadiah Yahyauddin - Aminullah, Rosita; Musahar, Roselina; Yahyauddin, Nadiah (2015)
ESL courses were taught classroom-based for more than 30 years in UiTM. Recently, blended learning was introduced and was considered as an innovative method in the ESL teaching and learning. In relation to that, this pilot study examines the attitudes and perceptions of UiTM students to gauge their readiness in using blended learning in their ESL courses. The study was conducted using a set of questionnaires through sampling of convenience. The data collected was analyzed using SPSS 18.0 to provide indicators on the students' attitudes and perceptions that would indicate their readiness for blended learning. A structured interview was also conducted to study the students' perceptions on the current use of blended learning and to probe some of the problems that students might face in blended learning. The study revealed the attitudes and perceptions of most students were positive and that they were ready for blended learning. However, certain areas need to be improved so that the use of blended learning can be maximized in the teaching and learning of the ESL courses.